A multi-agent system for recommending fire evacuation routes in buildings, based on context and IoT - Neto, Joaquim (2020)
The herein proposed research project brings together the area of the multi-agent recommender systems and the IoT and aims to study the extent to which a context-based multi-agent recommender system can contribute to improving efficiency in the evacuation of buildings under a fire emergency, recommending the most adequate and efficient evacuation routes in real time.